Cystic degeneration of a fibroid in the context of abnormal uterine bleeding in young patients: a case report - Juárez Menéndez, Noé Alonso; Arguelles Castillo, Cinthia Nallely; Tapia Navarro, Carolina; Reyes Hernández, Juan Armando; García Peña, Alejandro; Padrón Martínez, Rodolfo; Valderrama-Treviño, Alan Isaac (International Surgery Journal, 2025)
Uterine fibroids are the most common uterine tumors in perimenopausal women; their presence and growth are associated with elevated estrogen levels and stimulation of progesterone receptors. Clinically, fibroids are associated with abnormal uterine bleeding, anemia, recurrent pregnancy loss, infertility, and/or chronic pelvic pain. Ultrasound imaging faces challenges when fibroids present atypical features. Degenerated fibroids in their cystic variant are related to edema and multiple intrauterine cysts. In young patients, obstetric pathology should not be overlooked. The easy accessibility and low cost of ultrasound allow for universal screening of patients with abnormal uterine bleeding. The pathognomonic presence of a "cluster of grapes" pattern raises suspicion of molar pregnancy in this patient population. It is essential to establish an accurate diagnosis to initiate appropriate therapeutic management, prognosis, and follow-up. Gynecologists and sonographers should consider the β-hCG hook effect or receptor saturation, which may produce false-negative results, as well as recognize the degenerative variants of uterine fibroids to accurately raise diagnostic suspicion.